2020
DOI: 10.1097/mcg.0000000000001443
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Children With Inflammatory Bowel Disease

Abstract: Background: Vitamin D has anti-inflammatory and immune regulatory functions. Goals: The authors investigated the effect of vitamin D supplementation in children with inflammatory bowel disease (IBD) and hypovitaminosis D on disease activity, quality of life (QOL), inflammatory markers, and cytokines. Study: This randomized double-blinded controlled clinical trial included 120 children with IBD and hypovitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Of these biomarkers, fecal calprotectin (FC) correlates best with the number of active inflammation sites reported from biopsy than serum CRP and white blood cell count (15). Erythrocyte sedimentation rate (ESR), platelet count, and serum albumin level are also used to help assess IBD inflammation (54,55), though they are not particularly accurate measures of the disease.…”
Section: Traditional Plasma and Stool Biomarkers Used To Assess Ibd Activitymentioning
confidence: 99%
“…Of these biomarkers, fecal calprotectin (FC) correlates best with the number of active inflammation sites reported from biopsy than serum CRP and white blood cell count (15). Erythrocyte sedimentation rate (ESR), platelet count, and serum albumin level are also used to help assess IBD inflammation (54,55), though they are not particularly accurate measures of the disease.…”
Section: Traditional Plasma and Stool Biomarkers Used To Assess Ibd Activitymentioning
confidence: 99%
“…Vitamin D has the ability to inhibit the Th1 response related to the observed decreased in Th1related cytokines observed in their clinical study and previously performed in vitro studies (Sharifi et al, 2019). In contrary, vitamin D supplementation had clinical benefit in patients with both IBD and hypovitaminosis D, since the release of proinflammatory cytokines IL-2, IL-12, IL-13, and IL-17 were downregulated, suggesting suppression of the Th17 phenotype, whereas TNF-a levels were decreased, in contrast to the results of Sharifi et al (2019) (El Amrousy et al, 2020). Furthermore, vitamin D supplementation lowered the incidence of upper airway infections caused by the influenza virus investigated in patients with IBD (Arihiro et al, 2019).…”
Section: B Vitamin D Receptormentioning
confidence: 69%
“…Low serum vitamin D levels have been demonstrated to be associated with disease activity and with poorer clinical course in adult patients with IBD [ 109 ]. Recently, El Amrousy et al [ 110 ] conducted a double-blinded, randomized clinical trial on 120 children and adolescents affected by IBD and hypovitaminosis D who were randomized to receive either oral vitamin D3 in a dose of 2000 IU/day or placebo for 6 months. The authors reported that vitamin D supplementation was significantly inversely associated with clinical activity scores (PCDAI: 13.6 ± 3.1 in treatment group vs. 27.5 ± 3.5 in placebo group; PUCAI: 11.1 ± 2.4 in treatment group vs. 21.8 ± 2.9 in placebo group; p = 0.001) and with serum and fecal inflammatory markers (C-reactive protein (CRP), fecal calprotectin (FC) and pro-inflammatory cytokines).…”
Section: Nutritional Assessment and Supplementationmentioning
confidence: 99%